Estimation of Zinc level in anemic pregnant women and its relation to hemoglobin concentration - Huda Saleh Aldahmany,; Abdulwhab Aldei,; Mabroukah Mohamed Alzwayi, (Journal of Pure & Applied Sciences, 2022)
Background: Iron deficiency anaemia (IDA) is a major public health problem especially in underdeveloped and developing countries. IDA is the most prevalent nutrient deficiency during pregnancy.  Zinc is the co-factor of several enzymes and plays a role in iron metabolism, so zinc deficiency is associated with IDA. It is primary immunologic function in pregnancy and it also plays a critical role in hemoglobin synthesis and erythropoiesis. Objective: To investigate the prevalence of zinc deficiency in pregnant women with iron deficiency anemia, and its relation with the haematological parameters. Population: This study comprised 152 pregnant women; Women were divided into two groups according to the level of iron. Pregnant women with iron deficiency anaemia (n = 90) and pregnant women without iron deficiency anemia (n = 62). Materials and Methods: Data were collected using questionnaires and laboratory analyses of blood samples. The hematological parameters evaluated included haemoglobin, hematocrit, erythrocyte count, mean corpuscular hemoglobin (MCH), mean corpuscular volume (MCV) and mean corpuscular hemoglobin concentration (MCHC), Whereas biochemical analysis include serum ferritin, serum iron and zinc levels. Results: The mean zinc level was (44.4 ± 1.40 µg/dl) significantly lower in the IDA group than (53.5 ± 2.30 µg/dl) in those without IDA group (p < 0.05), and showed that Hb has a positive correlation with zinc (r = 0.303, P = 0.000) and other parameters. In short; zinc deficiency is more prevalent in women with IDA.